The Vertical Problem of COVID-19 in Indonesia: Differences in Concerns and Values between Government and Society - Nugraha, Tian Adhia (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
This study aims to deeply understand the care provided by Indonesian society and the government in addressing the COVID-19 issues in Indonesia. As is known, COVID-19 in Indonesia led to challenges in the economic and social sectors. In the early stages of COVID-19, the responses from the government and the public varied, with the government initially exhibiting apathy toward COVID-19. In contrast, the public independently took efforts to manage its spread. A qualitative research methodology was employed in this study. Data were collected through a literature review of relevant books, journals, and news sources. The study illustrated that the government and the public had their respective ways of addressing the spread of COVID-19. Despite the differences in approaches, both entities shared a common goal: to suppress the spread and resolve the issues related to COVID-19. The study briefly demonstrated the changes made by the government in its perception of COVID-19 and how the public's concern evolved. Two value positions emerged between the government and the public. First, when the government did not rely on scientific knowledge to assess COVID-19, it contrasted with a knowledgeable public. Second, when both the government and the public shared similar values regarding COVID-19, but employed different approaches to resolve conflicts. This study enriches theoretical discourse on the relationship between values, care, and public policy, highlighting that value differences between the state and society can serve as a foundation for constructive conflict resolution.